2022
DOI: 10.5213/inj.2142100.050
|View full text |Cite|
|
Sign up to set email alerts
|

Improved Urothelial Cell Proliferation, Cytoskeleton and Barrier Function Protein Expression in the Patients With Interstitial Cystitis/Bladder Pain Syndrome After Intravesical Platelet-Rich Plasma Injection

Abstract: Purpose: To investigate urothelial cell proliferation, cytoskeleton, inflammation, and barrier function protein expressions in patients with interstitial cystitis/bladder pain syndrome (IC/BPS) after intravesical platelet-rich plasma (PRP) injections Methods: A total of 19 patients with IC/BPS underwent 4 monthly intravesical PRP injections.Bladder biopsies were taken at the first and fourth PRP treatment. The bladder specimens were analyzed using the Western blot and immunochemical staining for progenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Expressions of urothelium Shh, CK5, ZO-1, E-cadherin, and transforming growth factor β also increased significantly after repeated PRP injections. By subgrouping according to PRP treatment outcomes, significant increases in Shh , E-cadherin, and ZO-1 expressions were noted only in patients with a GRA ≥ 1 or improved VAS but not in patients with a GRA of 0 and no improvement in VAS [ 73 ]. Besides the IC symptom scores, we could investigate the therapeutic efficacy of treatment for IC/BPS patients using the urothelial barrier markers, cytoskeletal maturation markers, and progenital cell markers ( Figure 3 ).…”
Section: Improvement Of Urothelial Regeneration In Ic/bps Bladders Af...mentioning
confidence: 99%
“…Expressions of urothelium Shh, CK5, ZO-1, E-cadherin, and transforming growth factor β also increased significantly after repeated PRP injections. By subgrouping according to PRP treatment outcomes, significant increases in Shh , E-cadherin, and ZO-1 expressions were noted only in patients with a GRA ≥ 1 or improved VAS but not in patients with a GRA of 0 and no improvement in VAS [ 73 ]. Besides the IC symptom scores, we could investigate the therapeutic efficacy of treatment for IC/BPS patients using the urothelial barrier markers, cytoskeletal maturation markers, and progenital cell markers ( Figure 3 ).…”
Section: Improvement Of Urothelial Regeneration In Ic/bps Bladders Af...mentioning
confidence: 99%
“…Immunohistochemistry study showed that four repeated PRP injections increased the expression of the urothelial cell proliferation marker Sonic hedgehog protein and cytoskeleton marker CK 5 , as well as the expression of adhesive proteins E-cadherin and ZO-1, in patients with IC/BPS, indicating that PRP injections can increase progenitor cell proliferative activity and facilitate barrier protein expression. ( Jhang et al, 2022 ). However, not all urothelial proteins show similar changes after PRP injection.…”
Section: Discussionmentioning
confidence: 99%
“…After four PRP injections in patients with IC/BPS, urinary levels of NGF, MMP-13, and VEGF decreased, and PDGF-AB levels significantly increased in responders, suggesting that PRP injections decrease inflammation, resulting in improvements in bladder pain and frequency episodes [ 48 ]. In addition, the expression of the urothelial barrier function protein and the urothelial cell proliferation protein increased after repeated PRP injections [ 49 ]. Thus, intravesical PRP injections may improve urothelial regeneration and differentiation to recreate a healthy urothelial barrier in IC/BPS bladders [ 50 ].…”
Section: Treatment Targeting Urothelial Dysfunction and Regenerative ...mentioning
confidence: 99%